Oxaliplatin-based second-line chemotherapy in neuroendocrine carcinomas. A case series and review of the literature - Galdy, Salvatore; Funicelli, Luigi; Luciani, Andrea; Giuffrida, Dario; Spada, Francesca; Cella, Chiara Alessandra; Murgioni, Sabina; Frezza, Anna Maria; Fazio, Nicola (European Journal of Oncology and Environmental Health, 2016)
Patients with metastatic gastroenteropancreatic neuroendocrine carcinomas (GEP-NECs) are generally treated with a first-line chemotherapy including cisplatin and etoposide, in the absence of randomized trials. No specific second-line regimen has been reported. According to some retrospective data, platinum rechallenge could be considered in GEP-NECs. However, in view of the considerable platinoid toxicity profile, it would be advisable to consider an analogue thereof in order to minimize cumulative toxicity. We present the clinical history of three metastatic GEP-NEC patients who underwent oxaliplatin-based second-line chemotherapy after progression on platinum-based first-line chemotherapy.